1 answer:
Answer:
The answer is C
Step-by-step explanation:
Let's solve your equation step-by-step.
4(x−2)=6x+18
Step 1: Simplify both sides of the equation.
4(x−2)=6x+18
(4)(x)+(4)(−2)=6x+18(Distribute)
4x+−8=6x+18
4x−8=6x+18
Step 2: Subtract 6x from both sides.
4x−8−6x=6x+18−6x
−2x−8=18
Step 3: Add 8 to both sides.
−2x−8+8=18+8
−2x=26
Step 4: Divide both sides by -2.
−2x/−2=26/−2
x=−13
Answer:
x=−13
You might be interested in
Answer:
i dont know
Step-by-step explanation:
Answer:
0.6 = 08
Step-by-step explanation:
Any second part or anything else to look at?
Answer:
the answer is 0.9988747935
hope that works!!
Answer:
1/27
plz mark brainest
Step-by-step explanation: